Identifying Complex Human Actions with a Hierarchical Feature Reduction and Deep Learning-Based Approach - Lakshmi Alekhya Jandhyam, Ragupathy Rengaswamy, Narayana Satyala (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Among computer vision’s most appealing and useful research areas is automated human activity recognition. In these systems, look and movement patterns in video clips are used to classify human behaviour. Nevertheless, the majority of previous research has either ignored or failed to employ time data to predict action identification in video sequences using standard techniques and classical neural networks. On the other hand, reliable and precise human action recognition requires a significant processing cost. To get over the challenges of the pre-processing stage, in this work, we choose a sample of frames at random from the input sequences. We only take the most noticeable elements from the representative frame rather than the entire set of attributes. We suggest a hierarchical approach in which bone modelling and a deep neural network are used first, followed by background reduction and HOG. For selecting features and historical data retention, a CNN along with LSTM recurrent network combo is taken into consideration; in the end, a SoftMax-KNN classification is employed to detect the human behaviours. The name of our model is represented by the abbreviation HFR-DL, which stands for a hierarchical Features Lowering & Deep Learning-based action detection approach. We utilize the UCF101 dataset, which is popular among action recognition researchers, for benchmarking in order to assess the suggested approach. There are 101 challenging tasks in the wild included in the dataset. When comparing the experimental results with eight cutting-edge methods, significant improvements in speed and accuracy are seen.